pH-responsive Vesicles with Tunable Membrane Permeability and Hydrodynamic Diameters from a Cross- linkable Amphiphilic Block Copolymer - Ruixue Chang; Yuelan Tian; Yong Wang; Jianglei Qin (Nanomaterials and Nanotechnology, 2016)
A series of cross-linked, pH responsive vesicles with tunable diameters were prepared by self-assembly of poly (ethyleneoxide)-b-poly [2-(diethylamino) ethyl methacry‐ late-co-glycidyl methacrylate,PEO-b-P(DEA-co-GMA)] in a THF/water mixture. The copolymers were synthesized by the random copolymerization of DEA and GMA, initiated by PEO-Br. With an epoxy group and a tertiary amine in its structure, self-catalysed cross-linking was triggered easily by mild heating. The vesicles showed pH responsiveness as characterized by DLS, and tunable permeability can be understood accordingly. As the pH of the solvent changed from 9.8 to 7.4, the diameters of the vesicles increased. It was observed that the diameters at pH = 6.0 were compa‐ rable to those at pH = 7.4. This alteration may have occurred because of the protonation of the PDEA segment. This particular property has great potential and many applica‐ tions, since most drug-loading and controlled-release studies are conducted within this pH range.